Science World [motion pictures] Chemistry : elements, compunds and mixture; - solutions : ionic and molecular. - Coronet (Northbrook, IL Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.
Vol 23: Elements, compunds and mixture; - Solutions : Ionic and molecular
Original copy in VHS format (VHS 23)
DVD Video
[Distributed by] International Book Center, Philippines
Keywords: Chemical Elements; Organic Compounds; Solutions (Chemistry); Ionic Solutions